Problem solving skills: esssential skills challenges for the 21st century graduates - Khairul Bariyyah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2021)
Problem solving skills are the abilities to identify problems, search and select various alternative solutions and make decisions in solving all the problems at hand. Problem solving skills are 21st century skills that are needed by society and the world of work. This research is a descriptive quantitative research. The research sample consisted of 300 students who were selected using the stratified random sampling technique. The research instrument used a scale of student problem solving skills. The Analysis of Data used descriptive analysis, independent sample t-test, and ANOVA with the help of the SPSS program. Based on the results of the study, it can be concluded (1) the average level of student problem solving skills is in the medium category (62.3%), (2) there is no significant difference in the level of student problem solving skills based on gender, (3) there is no significant difference in the level of student problem solving skills based on developmental status, (4) there is a significant difference in the level of problem solving skills of students based on age groups. The age group that has a significant effect on the difference in the average score of problem solving skills of students aged 23 years